Implementation of Management Information Systems in Primary Schools: A Qualitative Case Study - Khalis, Nur; Bahri, Saiful; Salfiyadi, Teuku (Yayasan Pendidikan dan Kemanusiaan Hurriah Aceh, 2025)
The growing digitalization of educational administration has established Management Information Systems (MIS) as vital instruments for enhancing school administration and facilitating decisions based on data. Despite its strategic importance, empirical data regarding the use of Management Information Systems in elementary education—especially in limited financial settings—remains uncommon. This study examines the planning, implementation, and evaluation of Management Information Systems (MIS) in SD Negeri 20 Kuta Makmur, a public primary school located in North Aceh Regency, employing a qualitative case study methodology, data were gathered via semi-structured interviews with school leaders, educators, and administrative personnel, supplemented by observations and document analysis. The results reveal that although the school exhibits a robust dedication to digital transformation, the efficacy of MIS implementation is hindered by insufficient infrastructure, restricted budgetary resources, and disparate digital competences among staff. Nonetheless, the technology has enhanced administrative coordination, data accessibility, and internal communication. The research indicates that effective MIS implementation relies on both technology preparedness and organizational elements, such as leadership dedication, well-defined operating protocols, and a conducive institutional culture. Without these enabling conditions, the transformational potential of digital technologies is only partially actualized. This research enhances the literature on educational digitalization by offering empirical observations from a primary school setting and presents practical implications for bolstering institutional capacity and governance in basic education via sustainable information system adoption